Introductory statistical genetics for plant breeding 1 - van Eeuwijk, Fred (Henry Stewart Talks, 2016)
Objectives of plant breeding, Definition, construction and identification of gene/genotype to phenotype (G→P) models, Genotype-Environment interaction, GxE, Phenotypic data, Causal and observational parameters
Archived at 2025/02/06